Getting the ability to have children back after surgery to take out uterine fibroids in older women - Razzakova Nilufar Saydaxmatovna; Qosimova Hadicha Jahongir qizi (Periodica Journal, 2025)
Clinical and factual examination of the farther comes about of myomectomy in arrange to assess the operation comes about in terms of recovery of richness ithin the late 18 patients of regenerative age who have fruitlessness was the most sign for surgery. It was uncovered that within the nearness of a single hub fibroids, non-deforming the uterine depth, for the realization of regenerative work strategy myomectomy (laparotomy / laparoscopy) isn't noteworthy.
Keywords: myomectomy; late reproductive age; ovarian reserve